ANTI-TYROSINASE ACTIVITY FROM VARIOUS SOLVENTS OF PEANUT SHELL (ARACHIS HYPOGAEA L.) EXTRACTS IN VITRO - FITHRIA, RISHA FILLAH; KRISDIANA, MELLA DWI; MUSLIMAH, ETIKA; MUSYAFA, SARIF; SUGIHARTINI, NINING (International Journal of Applied Pharmaceutics, 2019)
Objective: This study aimed to determine in vitro anti-tyrosinase activity from various solvents of peanut shell extracts and to find out if the activity is better than kojic acid which is a conventional compound used as anti-hyperpigmentation agent. Methods: Extraction was done by maceration method with various solvents of ethyl acetate, n-hexane, and 70% ethanol. Extracts were made into the series concentration of 25, 50, and 75 μg/ml. Kojic acid with concentration of 50 μg/ml used as positive control and 5% dimethyl sulfoxide used as negative control. Tyrosinase enzyme will react with L-3,4-dihydroxyphenylalanine substrate to produce dopachrome compound. The absorbance of dopachrome read by microplate reader at λ = 492 nm. If the absorbance read by the microplate reader is low, means that the inhibition power of the peanut shell extract against the tyrosinase enzyme is high. Anti-tyrosinase activity seen by the percentage inhibition value. The percentage inhibition value was analyzed with Kruskal–Wallis test followed by Mann–Whitney U-test; all tests were carried out with a confidence level of 95%. Results: The mean of percentage inhibition value of n-hexane extract ranged from 12.44 ± 1.66% to 39.82 ± 1.33%, 70% of ethanol extract ranged from 39.98 ± 0.85% to 70.19 ± 1.98%, and ethyl acetate extract ranged from 17.85 ± 0.78% to 60.30 ± 0.97%. Kojic acid has mean percentage inhibition value of 78.19 ± 1.97%. IC50 of ethanol, ethyl acetate, and n-hexane extracts was, respectively, 40.53 μg/ml, 63.49 μg/ml, and 91.95 μg/ml. Ethanol extract contains flavonoid, tannin, and saponin. Ethyl acetate extract contains flavonoid. Conclusion: All various solvents of peanut shell extracts have anti-tyrosinase activity but not better than kojic acid. Ethanol extract with concentration of 75 μg/ml has the greatest anti-tyrosinase activity.